ANALISIS PENGARUH CITRA MEREK, LOKASI DAN PROMOSI TERHADAP KEPUTUSAN ORANG TUA MURID MEMILIH JASA PENDIDIKAN MTs DI KKM MTsN PAMULANG - Ferdiansyah . (Inovasi, 2016)
ANALYSIS OF EFFECT OF BRAND IMAGE , LOCATION AND PROMOTION DECISION ON PARENTS EDUCATION STUDENTS CHOOSE MTS SERVICE IN KKM MTSN PAMULANGThe purpose of this study was to determine the extent of the influence of brand image, location and promotion to the decisions of parents choose the education services MTs using descriptive or descriptive quantitative research. The type of data used are primary data. For a population of 212 and the sample was 167 respondents . Methods of data collection is done by distributing a questionnaire with Likert scale. The results showed that (1) brand image positive and significant impact on the decision of parents, with the contribution value of 0.314. This means that the brand image influence the decision of parents of 31.4 %, (2) location positive and significant impact on the decision of parents, with the contribution value of 0.196. This means that the brand image influence the decision of parents of 19.6%, (3) promotion positive and significant impact on the decision of parents, with the contribution value of 0.303. This means that the brand image influence the decision of parents of 30.3 %, (4) brand image, location and promotion simultaneously positive and significant impact on the decision of parents, with the contribution value of 0.430. This means that the brand image, the location and the simultaneous promotion affects the decisions of parents of 43.0 %, while the value of 57% is explained by other variables outside independent variables in this study. Keywords: Brand image, location, promotion and Decision Parents